2020
DOI: 10.4067/s0718-52862020000200221
|View full text |Cite
|
Sign up to set email alerts
|

Spillover effects of economic complexity on the per capita GDP growth rates of Mexican states, 1993-2013

Abstract: The opening up of the Mexican economy completely transformed the growth dynamics of the per capita Gross Domestic Product (GDP) of the country's various states, with a clear tendency towards growth being concentrated in specific regions. In this study, we quantify the indirect or spillover effect of economic complexity on growth based on the following two facts: i) economic complexity is an important factor in explaining GDP growth rates, and ii) there is a clear regional pattern in the states' economic comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…World economies also promote the positive aspects of per capita GDP, which directly impacts the general economy as well as ASEAN economies that primarily emphasize on the importance of per capita GDP. It has been reported that the empowerment of per capita GDP directly initiates important measures that cultivate the sustainable means of economic development (Gómez-Zaldívar et al ., 2020). A similar situation is also depicted in the after-impacts of COVID-19 where world-leading economies strive to establish a sustainable environment (Pacana and Ulewicz, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…World economies also promote the positive aspects of per capita GDP, which directly impacts the general economy as well as ASEAN economies that primarily emphasize on the importance of per capita GDP. It has been reported that the empowerment of per capita GDP directly initiates important measures that cultivate the sustainable means of economic development (Gómez-Zaldívar et al ., 2020). A similar situation is also depicted in the after-impacts of COVID-19 where world-leading economies strive to establish a sustainable environment (Pacana and Ulewicz, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are variations in the rates of economic growth among regions, regardless of whether the countries are developed or developing, capitalist or socialist. According to Gómez‒Zaldívar et al, China has clearly made progress in comparison to other underdeveloped nations as the gap in relative income between its provinces and regions has shrunk [ 3 ]. The gap between the three major areas is much smaller than that indicated by per capita GDP, according to Chen's per capita net income for farmers and per capita disposable income in urban areas (gross domestic product).…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the ECI of Mexican states, we followed the studies that have done it previously – see Chávez et al (2017), Gómez‐Zaldívar et al (2020) and Gómez‐Zaldívar et al (2021) – all of whom used the methodology proposed by Hidalgo and Hausmann (2009) and employed data on the number of people employed (PE) by state and economic activity, such as information on the relative economic structure of the 32 states.…”
Section: Data and Methods To Estimate The Relationship Between Income...mentioning
confidence: 99%